Beyond the “empty forest”: The defaunation syndromes of Neotropical forests in the Anthropocene - Pires, Mathias M. [UNESP] (2023)
Human activities have altered the abundance and distribution of animals, reshaping ecosystems into novel and generally more depauperate configurations. Whereas, overhunting and habitat loss threaten numerous species, predation release and subsidies from agriculture and food waste benefit others. Although these impacts combined can generate multiple different outcomes, we propose that, depending on the prevalence of different anthropogenic drivers, mammalian communities are pushed towards one of three main defaunation syndromes: Herbivore-dominated, seed predator-dominated or mesopredator-dominated systems. The extirpation of top predators favors herbivore-dominated assemblages, while habitat loss and overhunting eliminate large-bodied herbivores, resulting in the dominance of smaller-bodied seed predators and mesopredators. Within fragmented landscapes where top predators are absent, mesopredator-dominated systems emerge supported by food subsidies from the surrounding agricultural matrix. Based on a large dataset of camera-trap studies, we show that continuous Neotropical forests with top predators exhibit a greater balance between these guilds and landscape structure explain composition variation according to these syndromes. The prevalence of one guild over others has profound effects on ecological processes, threatening ecosystem services and human health and may be the dominant scenario in the Anthropocene.